2017
DOI: 10.1371/journal.pone.0186981
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide potentiates platelet responses via toll-like receptor 4-stimulated Akt-Erk-PLA2 signalling

Abstract: Lipopolysaccharide (LPS) from the cell envelope of Gram-negative bacteria is a principal cause of the symptoms of sepsis. LPS has been reported to modulate the function of platelets although the underlying mechanisms of LPS action in these cells remain unclear. Platelets express the Toll-like receptor 4 (TLR4) which serves as a receptor for LPS, although the potential role of TLR4 and associated cell signalling in controlling platelet responses to LPS has not been extensively explored. In this study, we theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 61 publications
(91 reference statements)
2
59
0
Order By: Relevance
“…However, LPSstimulated platelets, which bind of fibrinogen (i.e. α IIb β 3 is activated) and also robustly activate NETosis independent of P-selectin (Clark et al, 2007;Looney et al, 2009;Lopes Pires et al, 2017;McDonald et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, LPSstimulated platelets, which bind of fibrinogen (i.e. α IIb β 3 is activated) and also robustly activate NETosis independent of P-selectin (Clark et al, 2007;Looney et al, 2009;Lopes Pires et al, 2017;McDonald et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies have shown that TLR4 activation by LPS induces platelet activation, most observed that this is not a direct effect but rather potentiates platelet responses elicited by classical agonists including aggregation, ATP release, P‐selectin expression, and the formation of mixed aggregates between platelets and neutrophils . It is worth mentioning that, among these studies, only the experiments by Nocella et al .…”
Section: Platelet Tlr4 Activation Promotes Platelet Pro‐thrombotic Anmentioning
confidence: 99%
“…Because SNARE complex formation is involved in platelet secretion, it could be conceivable that the NF‐κB pathway controls platelet secretion mediated by LPS, in particular when acting in combination with subthreshold thrombin concentrations. The observation that platelet stimulation with LPS plus thrombin or collagen triggers PI3K/AKT activation and that AKT phosphorylates IKK‐β renders IKK‐β a relevant potential role as a mediator of LPS‐induced platelet secretion. Moreover, this hypothesis appears to be more comprehensive as other TLR4 ligands such as cellular Fn‐EDA + potentiates thrombin‐induced IKK/NF‐κB activation in WT but not in TLR4‐/‐ platelets …”
Section: Platelet Tlr4 Expression and Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilitated by sCD14 derived from plasma [39], endotoxin binds to this receptor and initiates a signaling cascade that involves the adaptor protein MyD88, resulting in activation of the nitric oxide and cyclic guanosine monophosphatedependent protein kinase pathway. This is sufficient to induce secretion of dense and α-granules but does not induce platelet aggregation, as determined by ex vivo experiments [36][37][38]. Instead, endotoxin sensitizes and potentiates the aggregation response to subthreshold concentrations of…”
Section: Discussionmentioning
confidence: 97%